Impact of Dividend Stability on Car Manufacturers and Spare Part Manufacturers of Europe - Leskovskaya, Diana (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Dividend policy is an important part of the financial policy of modern companies and is one of the tools that ensures the investment attractiveness of the company. The mechanism of distribution of net profit has a special influence on the value of the company. In practice, the adoption of management decisions are carried out within the framework of the dividend policy. The implementation of an optimal dividend policy is one of the important areas of activity of a financial manager and requires a deep understanding of the impact on its factors as well as its relationships with other management decisions. The question of how to have an optimal dividend policy is one of the most discursive topic for researchers. This research will show how stable the dividend policy is for European car manufacturing and spare part manufacturing companies. These countries include Austria, Finland, France, Germany, Italy, Netherlands, Portugal, Spain and Sweden. In this study, we examine the dividend policies of 24 European automotive industry companies from 1998 to 2018. To understand the dividend distribution policy, we used the prominent Lintner’s model in a panel data setting. The results showed that the auto industry has a stable dividend policy. This finding is in line with the findings in developed and developing countries that companies use dividend smoothing. The main factors influencing the changes in the payment of cash dividends are past dividends and current earnings, and the most influential determinant is the level of lagged dividends. Keywords: Dividend Policy, Dividend Stability, Lintner’s Model

ÖZ:Temettü politikası, şirketlerin finans politikasının önemli bir parçası olup, şirketin yatırım çekiciliğini sağlayan araçlardan birisidir. Temettü dağıtım mekanizmasının şirket değeri üzerinde özel bir etkisi vardır. Optimal bir temettü politikasının uygulanması, bir finans yöneticisinin önemli kararlarından birisidir. Temettü politikası kararının diğer yönetim kararlarıyla olan ilişkilerinin derinlemesine anlaşılmasını gerektirmektedir. Optimal bir temettü politikasına nasıl sahip olunacağı sorusu, araştırmacılar tarafından tam olarak cevaplandırılmış bir soru değildir. Bu araştırma, Avrupalı otomobil ve yedek parçası üreten şirketlerin temettü politikalarının ne kadar istikrarlı olduğunu incelemektedir. Bu ülkeler arasında Avusturya, Finlandiya, Fransa, Almanya, İtalya, Hollanda, Portekiz, İspanya ve İsveç bulunmaktadır. Bu çalışmada, 1998'den 2018'e kadar 24 Avrupa otomotiv endüstrisi şirketinin temettü politikalarını inceliyoruz. Temettü dağıtım politikasını anlamak için, panel veri ortamında Lintner modeli kullanılmıştır. Sonuçlar, otomobil endüstrisinin istikrarlı bir temettü politikasına sahip olduğunu göstermektedir. Bu bulgu, gelişmiş ve gelişmekte olan ülkelerdeki bulgularla uyumludur. Nakit temettü ödemelerindeki değişiklikleri etkileyen ana faktörler geçmiş temettüler ve cari kazançlardır. En etkili belirleyici, geçmiş temettü seviyesidir. Anahtar Kelimeler: temettü politikası, temettü istikrarı, Lintner modeli.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Cahit Adaoğlu.
Keywords: Dividends-Taxation-Companies-Investments-Europe; investment-companies; Dividend Policy; Dividend Stability; Lintner’s Model